Micro-Raman Spectroscopy for the Determination of Local Temperature Increases in TiO2 Thin Films due to the Effect of Radiation. Issue 7 (July 2016) - Gallardo, Juan Jesús; Navas, Javier; Zorrilla, David; Alcántara, Rodrigo; Valor, Diego; Fernández-Lorenzo, Concha; Martín-Calleja, Joaquín
This study applied a classic method involving Raman spectroscopy and the use of Stokes and anti-Stokes peaks to measure the temperature of TiO2 thin films found in dye-sensitized solar cells (DSSCs). In addition, three mathematical formulae were used and analyzed to estimate the increase in temperature generated solely by the effect of the radiation. The tests and calculations performed showed an increase in the temperature of the TiO2 film. That is, the films were heated by the radiation they were exposed to. A temperature increase of up to 30 K was detected for the sample with a single layer of TiO2, and over 40 K for the sample with three layers for the highest radiation powers used, and greater increases in temperature were observed in the thicker films.